Choriocapillary vascular density changes in choroidal neovascularization associated with choroidal nevus after anti-VEGF injections. Issue 2 (March 2022) - D'andrea, Luca; Fossataro, Federica; Cennamo, Gilda
Purpose: To evaluate choriocapillary vascular density changes in choroidal neovascularization (CNV) type 2 associated with choroidal nevus using optical coherence tomography angiography (OCT-A) before and after anti-VEGF treatment. Methods: Observational case report. Results: A 25-year-old woman, was referred to Eye Clinic and presented a decreased visual acuity in right eye. Fundus examination showed a pigmented lesion located in macular region associated with subretinal hemorrhages adjacent to the mass in right eye. The diagnosis of choroidal nevus-associated with CNV was made and confirmed by spectral domain (SD)-OCT, OCT-A, and ultrasound examination. Two monthly ranibizumab intravitreal injections (IVT) were performed and a regression of the activity of neovascular lesion was noted. OCT-A showed a reduction of choriocapillaris vessel density (VD) before the treatment and an increase of VD after IVT injections. Conclusion: OCT-A could be a non-invasive and diagnostic tool to evaluate choriocapillaris vascular changes after IVT injections in CNV associated with choroidal nevus.